2020
DOI: 10.1021/acsptsci.0c00072
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ligand-Drug Conjugates Targeting Melanoma through the Overexpressed Melanocortin 1 Receptor

Abstract: Melanoma is a lethal form of skin cancer. Despite recent breakthroughs of BRAF-V600E and PD-1 inhibitors showing remarkable clinical responses, melanoma can eventually survive these targeted therapies and become resistant. To solve the drug resistance issue, we designed and synthesized ligand-drug conjugates that couple cytotoxic drugs, which have a low cancer resistance issue, with the melanocortin 1 receptor (MC1R) agonist melanotan-II (MT-II), which provides specificity to MC1R-overexpressing melanoma. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The stapling strategies developed in the bicyclic MCR peptides also provide opportunities for further transformations to build peptide conjugates and explore other drug design avenues. For example, MC1R has attracted attention as a potential molecular target for development of therapeutics and diagnostics in malignant melanoma because this receptor is overexpressed in a large proportion of these cell types. , Peptide conjugates, where an MCR-targeting epitope is linked to a cytotoxic molecule or diagnostic agent, are an attractive option, but the diversity of conjugation technologies employed in the context of MCR is almost exclusively reliant on amide-forming chemistry, typically requiring protected peptide substrates and often employing synthetic approaches that are difficult to rapidly diversify or to explore structure activity relationships. ,, This motivated us to further expand the bicyclic stapled peptide analogues by using functionalization chemistry on the unprotected peptide analogues to further build and evaluate how various linkers and payloads influence the pharmacology of the conjugates at MC1R.…”
Section: Resultsmentioning
confidence: 99%
“…The stapling strategies developed in the bicyclic MCR peptides also provide opportunities for further transformations to build peptide conjugates and explore other drug design avenues. For example, MC1R has attracted attention as a potential molecular target for development of therapeutics and diagnostics in malignant melanoma because this receptor is overexpressed in a large proportion of these cell types. , Peptide conjugates, where an MCR-targeting epitope is linked to a cytotoxic molecule or diagnostic agent, are an attractive option, but the diversity of conjugation technologies employed in the context of MCR is almost exclusively reliant on amide-forming chemistry, typically requiring protected peptide substrates and often employing synthetic approaches that are difficult to rapidly diversify or to explore structure activity relationships. ,, This motivated us to further expand the bicyclic stapled peptide analogues by using functionalization chemistry on the unprotected peptide analogues to further build and evaluate how various linkers and payloads influence the pharmacology of the conjugates at MC1R.…”
Section: Resultsmentioning
confidence: 99%
“…Bremelanotide (PT-141), an acid derivative of melanotan II, acts as an agonist of the MC1R and MC4R and has been demonstrated to increase erectile function and sexual desire (Figure 6) [112,113]. In 2020, Zhou et al reported an attractive study in which melanotan II was utilized as a probe for selective drug delivery [114,115]. The authors synthesized and designed ligand-drug conjugates with the melanocortin 1 receptor (MC1R) agonist melanotan-II (MT-II) to couple a cytotoxic drug, camptothecin with low cancer resistance (Figure 7).…”
Section: Melanotan II (Mt-ii)mentioning
confidence: 99%
“…This approach of drug-MT-II conjugates offers more options in cytotoxic drug selection and is noteworthy for potentially overcoming the cancer-resistant problem of melanoma. In 2020, Zhou et al reported an attractive study in which melanotan II was utilized as a probe for selective drug delivery [114,115]. The authors synthesized and designed ligand-drug conjugates with the melanocortin 1 receptor (MC1R) agonist melanotan-II (MT-II) to couple a cytotoxic drug, camptothecin with low cancer resistance (Figure 7).…”
Section: Melanotan II (Mt-ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…In cyclic versions, the Lys 11 is often replaced by Arg, suggesting that the Lys side chain is not necessary for receptorbinding affinity [17,18]. The α-MSH radiolabeled analogs have been predominantly used as diagnostic tools in the field of melanoma research, but only a few studies have investigated their chemotherapeutic applications [12,13,15,17,[19][20][21][22][23][24][25][26]. Melphalan (phenylalanine mustard: PAM) was attached either to the side chain of Lys in position 11 (because it is not part of the main receptor recognition site of α-MSH) or to the N-terminus; furthermore, the Arg 8 was replaced by PAM.…”
Section: Introductionmentioning
confidence: 99%